Carbon isotope signatures from land snail shells: Implications for palaeovegetation reconstruction in the eastern Mediterranean. (8th March 2017) - Prendergast, A.L.; Stevens, R.E.; Hill, E.A.; Hunt, C.; O'Connell, T.C.; Barker, G.W.
Abstract: In this study we compare carbon isotope values in modern Helix melanostoma shell carbonate (δ 13 Cshell ) from the Gebel al-Akhdar region of Libya with carbon isotope values in H. melanostoma body tissue (δ 13 Cbody ), local vegetation (δ 13 Cplant ) and soil (δ 13 Csoil ). All vegetation in the study area followed the C3 photosynthetic pathway. However, the δ 13 Cplant values of different species formed two distinct isotopic groups. This can be best explained by different water use efficiencies with arid adapted species having significantly more positive δ 13 Cplant values than less water efficient species. The ranges and means of δ 13 Cbody and δ 13 Cplant were statistically indistinguishable from one another suggesting that δ 13 Cbody was primarily a function of local vegetation composition. H. melanostoma δ 13 Cshell reflected the δ 13 Cplant of local vegetation with a positive offset between body/diet and shell of 14.5 ± 1.4‰. Therefore, in the Gebel al-Akhdar where only C3 plants are present, higher mean δ 13 Cshell values likely reflect greater abundances of water-efficient C3 plants in the snails diet and therefore in the landscape, whilst lower mean δ 13 Cshell values likely reflect the consumption of less water-efficient C3 plants. The distribution of these plants is in turn affected by environmental factors such as rainfall. These findings can be applied to archaeological and geological shell deposits to reconstruct late Pleistocene to Holocene vegetation change in the southeast Mediterranean.